Role of atom redeposition during rising ion flux in ion-induced nanodot self-assembly on GaSb surfaces. (5th September 2017) - Ranjan, Mukesh; Joshi, Purvee; Bhatnagar, Mukul; Mukherjee, Subroto
Abstract: In this study, a bottom-up approach of ion irradiation from hot cathode DC discharge plasma was used to investigate the role of energetic ion flux on the self-assembly of GaSb nanodots (NDs) at normal incidence. It was observed that, when increasing the flux in the range of 10 14 –10 15 ions cm −2 s −1, the lateral dimension and root mean square (RMS) roughness of NDs is reduced even at constant temperature conditions in the ion energy range from 400–800 eV. The evolution of the surface morphology for different flux regimes is observed in a numerical integration simulation using the nonlinear isotropic damped Kuramoto–Sivashinsky (DKS) equation. By introducing a redeposition term, the DKS equation is found to be in good qualitative agreement with the experimental results. We have demonstrated the linear dependency of the redeposition coefficient on the ion flux and also reported the nonlinear dependency on the thermal diffusion coefficient, transition time, and characteristic length with the flux. In accordance with the nonlinearity, we have also discussed the effect of the variation of the ion flux on the RMS roughness and lateral dimension of NDs.